2011
DOI: 10.1123/jtpe.30.4.375
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Instructional Approaches to Enhance Tactical Knowledge in Volleyball among University Students

Abstract: This study investigated the decision-making process of three instructional groups (i.e., teacher-centered, student-centered with tactical questioning and studentcentered without tactical questioning) in practical courses in volleyball among university students. All students (N = 122) performed a Tactical Awareness task on the correctness of the decision-making process at three testing phases (i.e., pretest, posttest and retention test). The results revealed that the tactical awareness of all students ameliorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
2
14
0
1
Order By: Relevance
“…The treatment group achievement was found to be higher than that of the control group. This shows that this finding is in line with previous studies [16,28,29] which showed that the reasoning achievement performance of student group who used TGfU Model is higher than that of student group who used Technical Model.…”
Section: Mean Reasoning Achievement By Itemsupporting
confidence: 92%
See 2 more Smart Citations
“…The treatment group achievement was found to be higher than that of the control group. This shows that this finding is in line with previous studies [16,28,29] which showed that the reasoning achievement performance of student group who used TGfU Model is higher than that of student group who used Technical Model.…”
Section: Mean Reasoning Achievement By Itemsupporting
confidence: 92%
“…This shows that the urban students mastered the reasoning skills better in net and wall games compared to the rural students. The result of this study was in line with previous studies [16,22,28,29] which showed that the reasoning achievement of TGfU group was higher than that of Technical groups. Urban students are more exposed to reasoning skills as the implementation of reasoning concept occurs in the teaching of all subjects in schools [30].…”
Section: Mean Reasoning Achievement By Itemsupporting
confidence: 92%
See 1 more Smart Citation
“…In a volleyball study, Broek, Boen, Claessens, Feys, and Ceux (2011) compared three teaching methodologies (traditional, comprehensive without the involvement of questions, and comprehensive with the involvement of questions). The results showed that in the latter, the significant differences between pretest and posttest were much higher than those of the other two groups, in terms of the tactics and decision-making variables.…”
Section: Discussionmentioning
confidence: 99%
“…Another opinion added, the difference in instructional style of teaching has the value of more effectiveness in the delivery of overall content in the delivery of information in the scope of sports games. The explanation is based on a quote, although the traditional instructional model might be effective in improving technical skills, it has been criticized for the loss of the contextual nature of the skills in sport games (Broek, Boen, and Claessens, 2015). Teaching style is a form of teacher's performance during the teaching and learning process both curricular and psychological.…”
Section: Introductionmentioning
confidence: 99%